Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more
Download
Standard view
Full view
of .
Look up keyword
Like this
3Activity
0 of .
Results for:
No results containing your search query
P. 1
ejercicios de Derivación

ejercicios de Derivación

Ratings: (0)|Views: 162|Likes:
Published by chevave322

More info:

Categories:Types, School Work
Published by: chevave322 on Aug 05, 2011
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

10/26/2012

pdf

text

original

 
ecnicas Mateaticas de Resoluci´on de Problemas
Curso 2005/2006
Escuela Universitaria de Ingenier´ıa ecnica Agr´ıcola Departamento de Matem´ atica Aplicada I 
Derivaci´on6 Derivadas
Ejercicio 6.1
Calcular la derivada de las siguientes funciones:(a.)
y
=
x
3
(b.)
y
=
x
8
(c.)
y
= 7
x
5
(d.)
y
=
34
x
4
(e.)
y
= 11
x
8
(f.)
y
=
x
1
0
x
7
+
x
4
(g.)
y
=
x
1
2 +
x
6
x
3
(h.)
y
=
x
7
+
x
4
x
(i.)
y
= 10
x
8
+ 4
x
4
5
x
(j.)
y
= 15
x
6
+ 9
x
3
2(k.)
y
= 5
x
6
+ 4
x
5
7
x
2
+ 9
x
12 (l.)
y
= 8
x
9
2
x
5
2
x
4
+ 2
x
+ 19(m.)
y
= 3
x
7
3
x
5
+ 12
x
4
4
x
9 (n.)
y
=
x
7
(o.)
y
=
x
2
(p.)
y
=
x
13
(q.)
y
=
1
x
4
(r.)
y
=
x
(s.)
y
=
3
x
(t.)
y
=
3
x
2
(u.)
y
=
4
x
3
(v.)
y
=
1
√ 
x
(w.)
y
=
1
3
√ 
x
(x.)
y
=
1
3
√ 
x
5
(y.)
y
=
1
7
√ 
x
4
(z.)
y
=
√ 
x
33
√ 
x
2
Ejercicio 6.2
Calcular la derivada de las siguientes funciones:(a.)
y
=
x
2
3
x
3
x
(b.)
y
=
x
3
3
x
2
x
2
x
(c.)
y
=
x
5
x
3
+
x
(d.)
y
=
x
2
+1
x
3
+1
(e.)
y
=
x
4
+
x
2
x
2
+1
(f.)
y
=
3
x
3
+1
x
4
+1
(g.)
y
=
2
x
+5
x
3
+
x
(h.)
y
=
x
5
x
3
x
(i.)
y
=
x
1
x
3
(j.)
y
=
ln
(3
x
) (k.)
y
=
ln
(
x
3
) (l.)
y
=
ln
|
x
|
(m.)
y
=
ln
(
x
2
+ 1) (n.)
y
=
ln
(2
x
3
+ 3
x
+ 1)(o.)
y
=
ln
(5
x
4
2
x
+ 5) (p.)
y
=
ln
(3
x
5
x
+ 4)(q.)
y
=
ln
(
x
6
+
x
4
+ 2
x
3
7) (r.)
y
= 3
x
(s.)
y
= 5
x
·
7
x
(t.)
y
=
3
x
6
x
(u.)
y
=
e
3
x
+1
(v.)
y
=
e
x
2
+
x
+1
(w.)
y
= 7
3
x
+1
(x.)
y
= 25
x
4
+
x
+1
(y.)
y
= 14
1
x
2
(z.)
y
= 2
x
3
+
x
2
1
Ejercicio 6.3
Calcular la derivada de las siguientes funciones:(a.)
y
=
sen
(3
x
+ 1) (b.)
y
=
sen
(
x
2
+ 1) (c.)
y
=
sen
(5
x
4
+ 7
x
+ 1)(d.)
y
=
sen
(3
x
4
+ 8) (e.)
y
=
sen
(
x
3
) (f.)
y
=
sen
(
lnx
)(g.)
y
= 3
sen
(
x
) (h.)
y
=
sen
(
x
)3
(i.)
y
=
sen
(
sen
(
x
))(j.)
y
=
sen
(3
x
) (k.)
y
= 7
cos
(
x
) (l.)
y
=
cos
(
x
)5
(m.)
y
=
cos
(3
x
+ 1) (n.)
y
=
cos
(
x
2
+ 1) (o.)
y
=
cos
(5
x
2
+ 7
x
+ 1)(p.)
y
=
cos
(5
x
4
7
x
2
) (q.)
y
=
cos
(
x
3
) (r.)
y
=
cos
(
ln
(
x
))(s.)
y
=
cos
(
cos
(
x
)) (t.)
y
=
cos
(3
x
) (u.)
y
=
arcsen
(
x
)(v.)
y
=
arcsen
(
x
2
) (w.)
y
= 7
arctg
(
x
) (x.)
y
=
arctg
(
x
)5
(y.)
y
=
arctg
(2
x
+ 1) (z.)
y
=
arctg
(3
x
2
+
x
)13
 
Ejercicio 6.4
Calcular la derivada de las siguientes funciones:(a.)
y
=
arctg
(
x
2
) (b.)
y
=
arctg
(
ln
(
x
)) (c.)
y
=
arctg
(
x
2
+
x
)
7
(d.)
y
= (2
x
2
+
x
3
)
6
(e.)
y
= (10
x
3
+ 8
x
4
+
x
)
10
(f.)
y
= (2
x
15
+ 2
x
3
)
8
(g.)
y
=
3
8
x
3
+ 2
x
2
(h.)
y
=
1
√ 
10
x
3
+
x
6
(i.)
y
=
k
3
√ 
2
x
5
+8
x
(j.)
y
=
10
7
x
5
+ 2
x
2
(k.)
y
=
10
x
12
+
x
3 (l.)
y
=
3
3
x
6
2
x
(m.)
y
=
5
6
(3
x
5
2
x
)
5
(n.)
y
= (10
x
4
+ 8
x
3
)(5
x
2
+ 2
x
)(o.)
y
= (40
x
3
+ 24
x
2
)(5
x
2
+ 2
x
) + (10
x
4
+ 8
x
3
)(10
x
+ 2)(p.)
y
= (7
x
3
+ 2
x
13
)(8
x
34
2
x
5
) (q.)
y
= (3
x
2
+
x
)(10
x
4
+ 8)(3
x
3
+ 2
x
)(r.)
y
= (4
x
3
+ 2
x
)(
x
+ 2
x
3
)(8
x
5
+ 2
x
) (s.)
y
=
3
x
5
8
x
2
+5
x
(t.)
y
=
30
x
3
+2
x
4
10
x
2
+8
(u.)
y
=
10
x
3
+2
x
8
x
5
7
x
3
(v.)
y
=
x
3
x
34
+8
(w.)
y
=
√ 
x
+2
3
√ 
x
2
+3
(x.)
y
=
(
x
2)
2
√ 
x
+5
(y.)
y
=
(3
x
2
2)
323
√ 
x
2
+5
x
(z.)
y
= 3
·
2
x
Ejercicio 6.5
Calcular la derivada de las siguientes funciones:(a.)
y
= (
ln
8)
x
(b.)
y
= 10
5
x
4
+
x
(c.)
y
= 8
3
x
6
2
x
(d.)
y
= 3
ln
(
x
)+
x
5
(e.)
y
= 10
(3
x
6
+2
x
)
4
(f.)
y
= 3
2
x
(g.)
y
= 8
ln
(
x
)
(h.)
y
=
e
4
x
3
+
ln
(
x
)+
e
x
(i.)
y
=
e
3
x
4
+
ln
(
x
)
(j.)
y
=
x
4
+2
x
3
2
x
4
2
x
(k.)
y
=
(2
x
3
+2
x
5
)
3
3
x
3
+2
x
(l.)
y
=
8
x
+
e
x
ln
(
x
)5
x
2
+
ln
(
x
3
)
e
x
4
(m.)
y
= (
x
3
+ 1)
4
x
2
1(n.)
y
=
ln
(
 
1+
√ 
x
1
√ 
x
) (o.)
y
= (5
x
3
+ 2
x
)
·
10
x
(p.)
y
= 5
x
ln
(
x
)(q.)
y
=
 
(
x
1)(8 +
x
) (r.)
y
= (3
x
+ 2
x
3
5
x
2
)
34
·
e
ln
(
x
)+
e
x
(s.)
y
=
arcsen
(
ln
(
x
)) (t.)
y
=
(3
x
2
+
e
x
)(
ln
(
e
x
2
)+2)
5
x
ln
(
x
2
)
(u.)
y
=
sen
(
 
ln
(
x
) +
x
)(v.)
y
=
arctg
(
xsen
(
x
)) (w.)
y
=
sen
(
x
+
sen
(
x
2
5
x
)
2
)(x.)
y
=
sen
(
x
)
sen
x
3
+ 2 (y.)
y
=
cos
3
x
2
e
2
x
Ejercicio 6.6
Calcula la derivada de las siguientes funciones:(a.)
y
=
3
2
x
3+2
x
(b.)
y
=
 
x
1
x
+1
(c.)
y
=
 
1 +
x
(d.)
y
= (
x
a
)
2
ax
x
2
+
a
2
arcsen
(
x
aa
) (e.)
y
=
√ 
x
 
2
4
x
2
+
12
arcsen
(
x
2
)(f.)
y
=
xsen
(
1
x
) +
1
x
2
(g.)
y
=
arctg
(
1+
x
1
x
)(h.)
y
=
ln
(
x
+
1 +
x
2
) (i.)
y
= ln(ln(
tg
(
x
)))(j.)
y
=
x
[
sen
(ln(
x
))
cos
(ln(
x
))] (k.)
y
=
arctg
(
sen
(ln(
cos
(
x
))))(l.)
y
=
e
x
(1
e
x
)ln(1
x
)
(m.)
y
=
tg
(
x
cos x
) (n.)
y
=
cos
(
x
tg
(
x
)
)(o.)
y
= (
e
x
)
e
x
(p.)
y
=
x
x
x
(q.)
y
=
   
x
(r.)
y
= (
arctg
(
x
))
arctg
(
x
)
(s.)
y
= ln(
arctg
(
x
) +
e
x
sen
(
cos
(
x
)))(t.)
y
=
tg
(
tg
(
tg
(
x
))) (u.)
y
=
tg
(
x
)
sen
(
x
)
cos
(
x
)
(v.)
y
=
x
 
sen
(
x
) +
cos
(
x
)14
 
(w.)
y
=
x
2
+1
xsen
(
x
)
(x.)
y
=
 
2
x
+53
x
(y.)
y
=
cos
2
(
cos
(
cos
(
x
)))
Soluci´on 6.1
a.) 3
x
2
; b.) 8
x
7
; c.) 35
x
4
; d.) 3
x
3
; e.) 88
x
7
; f.) 10
x
9
7
x
6
+ 4
x
3
g.)12
x
11
+6
x
5
3
x
2
; h.) 7
x
6
+4
x
3
1; i.) 80
x
7
+16
x
3
5; j.) 90
x
5
+27
x
2
; k.) 30
x
5
+20
x
4
14
x
+9;l.) 72
x
8
10
x
4
8
x
3
+ 2; m.) 21
x
6
15
x
4
+ 43
x
3
4; n.)
7
x
8
; o.)
2
x
3
; p.)13
x
2
/
3
; q.)
4
x
5
; r.)12
x
; s.)13
x
2
/
3
; t.)23
x
1
/
3
; u.)34
x
1
/
4
; v.)
12
x
3
/
2
; w.)
13
x
4
/
3
; x.)
53
x
8
/
3
; y.)
47
x
11
/
7
; z.)56
x
1
/
6
Soluci´on 6.2
a.)
(
x
4
8
x
2
+ 3)
x
2
(
x
2
1)
2
; b.)
x
2
2
x
+ 3(
x
1)
2
; c.)
(2
x
3
15
x
2
5)
x
2
(
x
2
+ 1)
2
;d.)
x
(
x
3
+ 3
x
2)(
x
3
+ 1)
2
; e.)4
x
5
+ 4
x
3
2
x
2
+ 1)(2
x
2
+ 1)
2
; f.)
x
2
(3
x
4
+ 4
x
9)(
x
4
+ 1)
2
;g.)
(4
x
3
+ 15
x
2
+ 5)
x
2
(
x
2
+ 1)
2
; h.)
(2
x
3
15
x
2
+ 5)
x
2
(
x
2
1)
2
; i.)3
2
xx
4
; j.)1
x
; k.)3
x
;l.)12
x
; m.)2
xx
2
+ 1; n.)3(2
x
2
+ 1)2
x
3
+ 3
x
+ 1; o.)2(10
x
3
1)5
x
4
2
x
+ 5; p.)15
x
4
13
x
5
x
+ 4;q.)2
x
2
(3
x
3
+ 2
x
+ 3)
x
6
+
x
4
+ 2
x
3
7; r.) 3
x
ln(3); s.) 35
x
ln(35); t.)
2
x
ln(2);u.) 3
e
3
x
1
; v.)
e
x
2
+
x
(2
ex
+
e
) ; w.) 3
·
7
3
x
+1
ln(7); x.) 2
·
5
2(
x
4
+
x
+1)
(4
x
3
+ 1)2ln(5);y.)
2
2
x
2
7
1
x
2
x
ln(14) ; z.) 2
x
3
+
x
2
1
x
(3
x
+ 2)ln(2)
Soluci´on 6.3
a.) 3cos(3
x
+ 1); b.) 2
x
cos(
x
2
+ 1); c.) (20
x
3
+ 7)cos(5
x
4
+ 7
x
+ 1);d.) 12
x
3
cos(3
x
4
+ 8) ; e.) 3
x
2
cos(
x
3
) ; f.)cos(ln(
x
))
x
g.) 3cos(
x
); h.)cos(
x
)3;i.) cos(
x
)cos(sin(
x
)) ; j.) 3
x
ln(3)cos(3
x
) ; k.)
7sin(
x
); l.)
sin(
x
)5;m.)
3sin(3
x
+ 1); n.)
2
x
sin(
x
2
+ 1); o.)
(10
x
+ 7)sin(5
x
2
+ 7
x
+ 1);p.) 2
x
(7
10
x
2
)sin(5
x
4
7
x
2
); q.)
3
x
2
sin(
x
3
) ; r.)
sin(ln(
x
))
x
; s.) sin(
x
)sin(cos(
x
));t.)
3
x
ln(3)sin(3
x
) ; u.)12
x
1
x
; v.)2
x
1
x
4
; w.)7
x
2
+ 1; x.)15(
x
2
+ 1);y.)12
x
2
+ 2
x
+ 1; z.)6
x
+ 19
x
4
+ 6
x
3
+
x
2
+ 1
Soluci´on 6.4
a.)2
xx
4
+ 1; b.)1
x
(ln(
x
)
2
+ 1); d.) 6
x
11
(
x
+ 2)
5
(3
x
+ 4);e.) 10
x
9
(8
x
3
+10
x
2
+1)
9
(32
x
3
+30
x
2
+1); f.)
3(5
x
12
+ 1)32
x
25
(
x
12
+ 1)
9
; g.)
2
4
/
3
(
x
+ 6)(
x
+ 4)
1
/
3
3
x
2
(
x
+ 4);h.)
3(
x
3
+ 5)
 
x
3
(
x
3
+ 10)
x
4
(
x
3
+ 10)
2
; i.)
2
2
/
3
k
(5
x
4
+ 4)6
x
4
/
3
(
x
4
+ 4)
4
/
3
; j.)
x
(35
x
3
+ 4)10(7
x
3
+ 2)
9
/
10
x
9
/
5
;k.)20
x
+ 12
10
x
2
+
x
3; l.)2(9
x
5
1)3(
x
(3
x
5
2))
2
/
3
; m.)25(2
15
x
4
)6(
x
(3
x
4
2))
11
/
6
; n.) 4
x
3
(75
x
2
+75
x
+16);15

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->